Nahdlatul Ulama: Bebas untuk Oportunis? Menelisik Kontestasi Politik pada Pemilihan Kepala Daerah Kabupaten Banyumas Periode 2008 dan 2013 - Rahmi Hasyﬁ Febrina; Bangun Udi Mustika; Adek Risma Dedees (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2014)
Nahdlatul Ulama as a religious organization, as independence intermediary organs which is helped the people to represent their interest between public aﬀ airs to the state. NU is not seen as opportunistic religion organization and a shamed organization cause of its ideology. More than, NU on politic arena, att empt to return as a religion organization which is has a greatest vission for making importance agenda and welfare of the members of a religion community (umat) life. Unbalancing support of NU at two periods of head of province or district election in Banyumas region on 2008 and 2013 explained that NU stood up to the fortiﬁ cation which likely could guarantee of NU’s interest. It does not care about ‘inconsistent’ stigma which is marked to NU. Thus, welfare and interest of umat are more importance than just having adorationas ‘consistence’ and ‘sportive’ religion organization in Banyumas, generally in politic arena. This research is qualitative-interpretative approach. The method is used observation, indeep interview and also utilizing secunder data and documentation matt ers.